Antiviral effects of Pediococcus acidilactici isolated from Tibetan mushroom and comparative genomic analysis - Niu, Tianming; Jiang, Yuxin; Fan, Shuhui; Yang, Guilian; Shi, Chunwei; Ye, Liping; Wang, Chunfeng (Frontiers in Microbiology, 2023)
Rotavirus is one of the main pathogens that cause diarrhoea in young animals, and countless animals have died of rotavirus infection worldwide. Three strains of lactic acid bacteria isolated from Tibetan mushrooms were used to study the inhibition of rotavirus in vitro and in vivo. One part was to identify and study the biochemical and probiotic characteristics of three isolated lactic acid bacteria, and the other part was to evaluate the inhibitory effect on rotavirus via in vivo and in vitro experiments. The whole genome of the lactic acid bacteria with the best antiviral effect was sequenced, and the differences between them and the standard strains were analyzed by comparative genomic analysis, so as to provide a theoretical basis for exploring the antiviral effect of lactic acid bacteria.The three strains were identified as Pediococcus acidilactici, Lactobacillus casei and Lactobacillus paracasei. Pediococcus acidilactici showed good acid tolerance, bile salt tolerance, survival in artificial intestinal fluid, survival in gastric fluid and bacteriostasis. In in vitro experiments, pig intestinal epithelial cells cocultured with Pediococcus acidilactici exhibited reduced viral infection. In the in vivo experiment, the duodenum of mice fed Pediococcus acidilactici had extremely low numbers of virus particles. The total genome size was 2026809bp, the total number of genes was 1988, and the total length of genes was 1767273bp. The proportion of glycoside hydrolases and glycoside transferases in CAZy was 50.6% and 29.6%, respectively. The Metabolism function in KEEG had the highest number of Global and overview maps. Among the comparative genomes, Pediococcus acidilactici had the highest homology with GCF 000146325.1, and had a good collinearity with GCF 013127755.1, without numerous gene rearrangement events such as insertion, deletion, inversion and translocation. In conclusion, Pediococcus acidilactici was a good candidate strain for antiviral probiotics